The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/pde.12795
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Levels Not Associated with Atopic Dermatitis Severity

Abstract: Levels of 25-hydroxyvitamin D were deficient or insufficient in 85% of the children, but serum vitamin D concentrations were not significantly related to AD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
2
16
3
3
Order By: Relevance
“…Our findings for atopic dermatitis and IgE agree with recent observational studies and RCTs [3,4,9]. In contrast, we have used the same methods to provide evidence supporting a causal role for 25OHD in risk of multiple sclerosis [41].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings for atopic dermatitis and IgE agree with recent observational studies and RCTs [3,4,9]. In contrast, we have used the same methods to provide evidence supporting a causal role for 25OHD in risk of multiple sclerosis [41].…”
Section: Discussionsupporting
confidence: 88%
“…Dark phototypes have not been previously associated with lower AD prevalence Regarding AD severity, patients with more severe forms tended to have lower serum 25(OH)D levels, although these were not statistically significant. These results are not supported by the findings of several studies, although others have reported a significant inverse correlation . Few studies have considered the influence of phototype when investigating this relationship .…”
Section: Discussioncontrasting
confidence: 68%
“…All of these functions support its role in the pathophysiology of AD . While low serum levels of VD have been linked to AD severity in certain populations, these findings have not been replicated in others . Therefore, the evidence to support the improvement of AD with VD supplementation is still weak …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in other studies, the correlations of low vitamin D with SCORAD, allergic sensitization, and high IgE were noted, but we did not find such associations. The recent publications also denied the thesis, that serum vitamin D concentrations were significantly related to AD severity . The role of vitamin D in immunoregulation, involving pro‐inflammatory cytokine synthesis, has been well described .…”
Section: Discussionmentioning
confidence: 99%